Nrf2 regulates gene-environment interactions in an animal model of intrauterine inflammation: Implications for preterm birth and prematurity - Sussan, Thomas E. (Sci Rep, 2017)
Preterm birth (PTB) is the leading cause of neonatal mortality, and surviving infants are at increased risk for lifelong disabilities. Intrauterine inflammation is an etiological factor that drives PTB, and oxidative stress is associated with PTB. Nuclear erythroid 2-related factor 2 (Nrf2) is a redox-sensitive transcription factor that is the key regulator of the response to oxidative and inflammatory stress. Here, we used the established mouse model of intrauterine inflammation-induced PTB to determine whether Nrf2 is a modifier of susceptibility to PTB and prematurity-related morbidity and mortality in the offspring. We determined that Nr2-deficient (Nrf2(−/−)) mice exhibited a greater sensitivity to intrauterine inflammation, as indicated by decreased time to delivery, reduced birthweight, and 100% mortality. Placentas from preterm Nrf2(−/−) mice showed elevated levels of markers of inflammation, oxidative stress, and cell death, and transcriptomic analysis identified numerous key signaling pathways that were differentially expressed between wild-type (WT) and Nrf2(−/−) mice in both preterm and control samples. Thus, Nrf2 could be a critical factor for gene-environment interactions that may determine susceptibility to PTB. Further studies are needed to determine if Nrf2 is a viable therapeutic target in women who are at risk for PTB and associated complications in the affected offspring.